2020
DOI: 10.48550/arxiv.2011.05256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spin Susceptibility Above the Superfluid Onset in Ultracold Fermi Gases

Yun Long,
Feng Xiong,
Colin V. Parker

Abstract: Ultracold atomic Fermi gases can be tuned to interact strongly, where they display spectroscopic signatures above the superfluid transition reminiscent of the pseudogap in cuprates. However, the extent of the analogy can be questioned, since thermodynamic quantities in the low temperature spin-imbalanced normal state can be described successfully using Fermi liquid theory. Here we present spin susceptibility measurements across the interaction strength-temperature phase diagram using a novel radiofrequency tec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…1 (depicted by the red circle in the top panel) differs by roughly two standard deviations from the AFQMC results. Very recently, new experimental data for the spin susceptibility of the UFG became available [30]. In the corresponding study, consistency with a mean-field approach was found, suggesting Fermi-liquid-type behavior.…”
Section: Numerical Results For the Spin Susceptibilitymentioning
confidence: 73%
See 2 more Smart Citations
“…1 (depicted by the red circle in the top panel) differs by roughly two standard deviations from the AFQMC results. Very recently, new experimental data for the spin susceptibility of the UFG became available [30]. In the corresponding study, consistency with a mean-field approach was found, suggesting Fermi-liquid-type behavior.…”
Section: Numerical Results For the Spin Susceptibilitymentioning
confidence: 73%
“…In spin- 1 2 systems with weak attractive interactions, for example, pairing of spin-up and spin-down particles at diametrically opposite points of the Fermi surface (i.e., Cooper pairing) typically leads to a superfluid phase at low enough temperatures, accompanied by the opening of an energy gap in the quasiparticle spectrum. Similar conclusions hold for strongly correlated systems, where pairing and superfluidity have been addressed thoroughly in theory [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and experiment [20][21][22][23][24][25][26][27][28][29][30]. A central open question in this regard is whether signatures of strong pairing fluctuations survive in the normal, non-superfluid high-temperature phase, which is often referred to as a "pseudogap regime", obtaining its name from a (potentially strong) suppression of the single-particle density of states around the Fermi surface.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation